A pilot study of a modification EAT-26 questionnaire for screening pathological eating behavior in competitive athletes - Stackeová, Daniela; Barešová, Tereza; Přibylová, Barbora (Frontiers in Psychology, 2023)
This study deals with pathological forms of eating behavior and disorders of athletes with the aim to verify a newly created questionnaire method focused on their screening. First, a detailed analysis of one of the most frequently used methods, EAT-26, was carried out, which was subsequently reworked into a newly created questionnaire that should meet the criteria for application to a group of competitive athletes. This new questionnaire was then verified on a group of athletes in risky sports disciplines. It was distributed among athletes of aesthetic sports, specifically among aerobics (gymnastic, sport, and fitness), gymnastics (modern and sport), professional dance, figure skating, and bodybuilding/fitness (classic bodybuilding, bikini fitness, and men’s physique). In total, 100 respondents, 79 women and 21 men, with 20 persons from each sport branch, aged 16–26, participated in the research. The main results of the research investigation were determined using factor analysis, which yielded positive results. Five strong factors (dietary control, body weight control, training obsession, appetite, and calorie counting) were identified, which can be defined as common and well-known characteristics in the eating and training regime of competitive athletes. At the same time, the factors found can be defined as essential factors influencing the emergence of disturbed eating behavior or the later development of an eating disorder. Compared to the original EAT-26, the point score was adjusted, and its critical value was determined at 57 points. Of the respondents, 33%, i.e., 33 out of a possible 100, achieved this value or above. Respondents with a point score of 57 and above were found in every sport tested. Of the 33 respondents reaching this point limit, 6% were in aerobics, 24% in gymnastics, 15% in professional dance, 27% in figure skating, and 27% in bodybuilding/fitness. Respondents from the bodybuilding and fitness sports sector achieved the highest number of points on average and those were the only ones who exceeded the threshold of 57 points on average. The results of the work correspond with the opinion of many experts that the sports environment is ideal for covering up disturbed eating behavior or eating disorders, and diagnosis in this environment is difficult.